Clinical significance of MMP-9 overexpression in endometrial cancer: A PRISMA-compliant meta-analysis - Li, Xia; Zha, Li; Li, Bo; Sun, Rong; Liu, Jianhua; Zeng, Hongwei (Frontiers in Oncology, 2022)
Objective: Several studies have found that MMP-9, one of the extracellular matrix-degrading proteinases, was involved in endometrial cancer’s clinical progression and prognosis. However, the associations of MMP-9 expression with risk, clinical features and prognosis of endometrial cancer were conflicting. Therefore, we performed the systematic review and meta-analysis to clarify the correlation of MMP-9 expression with endometrial cancer. Methods: Relative studies involving the associations between MMP-9 expression and endometrial cancer were retrieved from PubMed, Embase, Web of Science and CNKI (China National Knowledge Infrastructure) databases. OR (odds ratio) with 95% CI (confidence interval) was applied to evaluate the associations of MMP-9 expression with risk and clinical features of endometrial cancer. Furthermore, we evaluated the role of MMP-9 expression in prognosis of endometrial cancer using HR with 95% CI. The funnel plots and Begg test were used to assess the publication bias. Results: A total of 28 eligible studies were acquired from Pubmed, Embase, Web of science and CNKI databases. The present study found a significant association of MMP-9 overexpression with risk of endometrial cancer (OR = 11.02, 95% CI = 7.51-16.16, P < 0.05). MMP-9 overexpression was significantly associated with tumor grade, FIGO stage, lymph node metastasis and myometrial invasion (Tumor grade: OR = 1.68, 95% CI = 1.09-2.58, P < 0.05; FIGO stage: OR = 3.25, 95% CI = 1.73-6.08, P < 0.05; Lymph node metastasis: OR = 2.98, 95% CI = 1.27-7.03, P < 0.05; Myometrial invasion: OR = 2.42, 95% CI = 1.42-4.12, P < 0.05) in Asians. In addition, the overall results showed that MMP-9 overexpression predicted a worse prognosis of endometrial cancer (OR = 1.82, 95% CI = 1.01-2.62, P < 0.05). Conclusions: MMP-9 overexpression might be a potential predictor of poor clinical progression and prognosis of endometrial cancer.